2016
DOI: 10.4238/gmr15048008
|View full text |Cite
|
Sign up to set email alerts
|

Association of interferon-induced helicase C domain (IFIH1) gene polymorphisms with systemic lupus erythematosus and a relevant updated meta-analysis

Abstract: ABSTRACT. Systemic lupus erythematosus (SLE) is a complex autoimmune disorder presenting heterogeneous clinical manifestations.A number of genes involved in SLE susceptibility are related to the type I interferon (IFN) pathway. IFN mediates innate immune responses and its increased levels contribute to the breakdown of peripheral tolerance. Interferon-induced helicase C domain 1 (IFIH1) activates and modulates IFN responses through its caspase recruitment domain. In this study, we analyzed four IFIH1 single nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…[18][19][20][21][22][23] IFIH1 is found in various immune system cells and is involved in autoimmune disorders such as SLE. 24 IFIH1 increased IFN production by activation of NF-kB, IFNregulatory factors 3 and 7. 5,6 For the first time, we confirmed that IFIH1 rs3747517 plays a beneficial role in Egyptian children and adolescents with SLE.…”
Section: Discussionmentioning
confidence: 91%
“…[18][19][20][21][22][23] IFIH1 is found in various immune system cells and is involved in autoimmune disorders such as SLE. 24 IFIH1 increased IFN production by activation of NF-kB, IFNregulatory factors 3 and 7. 5,6 For the first time, we confirmed that IFIH1 rs3747517 plays a beneficial role in Egyptian children and adolescents with SLE.…”
Section: Discussionmentioning
confidence: 91%